2012
DOI: 10.2215/cjn.09090911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of Mutations in Sodium Phosphate Cotransporters

Abstract: SummaryThree families of sodium phosphate cotransporters have been described. Their specific roles in human health and disease have not been defined. Review of the literature reveals that the type II sodium phosphate cotransporters play a significant role in transepithelial transport in a number of tissues including kidney, intestine, salivary gland, mammary gland, and lung. The type I transporters seem to play a major role in renal urate handling and mutations in these proteins have been implicated in suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 103 publications
1
53
0
2
Order By: Relevance
“…Hyperphosphatemia has been identified in the past decade as a strong predictor of mortality in patients with advanced CKD (4,27,28). More recent studies have shown that the association between HP concentrations and higher mortality is not restricted to persons with renal disease ; it can also be observed in persons with cardiovascular disease and even in the general population (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperphosphatemia has been identified in the past decade as a strong predictor of mortality in patients with advanced CKD (4,27,28). More recent studies have shown that the association between HP concentrations and higher mortality is not restricted to persons with renal disease ; it can also be observed in persons with cardiovascular disease and even in the general population (29).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hyperparathyroidism, induced by hyperphosphatemia and 1,25 -(OH)2 vitamin D3 deficiency, is accompanied by parathyroid hyperplasia and excessive synthesis and secretion of parathyroid hormone, which results in renal osteodystrophy (4 -6). These pathologies have established the concept of CKD-mineral and bone disorder (CKD-MBD), which recognizes that CKD leads to higher morbidity and mortality due to cardiovascular disease and poor life prognosis (1,2,4). In response, a treatment strategy that emphasizes life prognosis has been recommended throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…The NaPi transporter SLC34 is mainly responsible for Pi homeostasis in the body (1,4). Three members of the SLC34 transporter family (SLC34A1-3) have been identified.…”
Section: Intestinal and Renal Phosphate (Re)absorption Via Napi Transmentioning
confidence: 99%
“…Mutation of NaPI-IIc causes autosomal recessive disorder hereditary hypophosphatemic rickets with hypercalciuria (HHRH) (4,10). Clinical studies suggest that HHRH is a primary renal Pi wasting disorder, resulting in increased serum 1,25-dihydroxyvitamin D3 concentrations with associated intestinal Ca 21 hyperabsorption, hypercalciuria, and rickets/osteomalacia.…”
Section: Phosphate Transporter and Related Diseasementioning
confidence: 99%
“…Emerging details on phosphate metabolism have identified a family of sodium phosphate transporters that help reabsorb the bulk of the filtered phosphate in the proximal tubule (66). These transporters appear to be affected by a series of factors, including the recently characterized fibroblast growth factor 23 and its obligate coreceptor Klotho, which together, via the fibroblast growth factor receptor, inhibit the reabsorption of sodium-dependent phosphate reabsorption and lower vitamin D levels by downregulating the gene for 1a-hydroxylase (67).…”
Section: Divalent Cations and Phosphate Homeostasismentioning
confidence: 99%